Seduction and Fidelity: Cunning and Power Relationships an Ethnographic Exploration in an Intensive Care Unit During the Covid-19 Crisis - Philippe, Bonneels (Nursing philosophy, 2025)
Sedufidelity—the contraction of seduction and fidelity—offers an interesting perspective for reflecting on the role of relationships and the ethics of care in highly technical healthcare settings. Understanding sedufidelity could help mitigate the observed social ruptures and promote a more humane approach to healthcare. However, challenges remain regarding its implementation, particularly in terms of building trust and loyalty towards management and healthcare policymakers. Furthermore, initiatives such as the ‘haie de déshonneur’ (‘hedge of dishonour’) can highlight the need and form of recognition sought by caregivers, given their strong symbolism. However, other actions can also be considered to strengthen relationships and attention paid to caregivers, such as a prior consultation.